Factors Affecting Difficulty of English Pre-Nominal Adjective Order for Saudi Learners - Manal Saleh M. Alghannam (Forum for Linguistic Studies, 2024)
The purpose of this paper is to illuminate foreign learners’ receptive mastery of the distinctive pre-nominal adjective order of English and factors affecting their correctness, using Saudi learners as an example. Although English adjective order itself is well-understood, second language learners’ acquisition trajectory is under-researched. In this study, 134 L1 Arabic learners responded to a multiple-choice test of adjective order knowledge in all possible two- and three-adjective prenominal sequences taken from the underlying accepted English sequence: quality - size - age - colour - nationality. Findings predominantly showed that there was some support for non-contrastive factors influencing sequence difficulty: the shorter sequences (i.e., of two adjectives) were easier than longer sequences, as were positions closer to the noun head in the underlying sequence (i.e., nationality) compared with those further away (e.g., quality). A factor not attested in previous studies was positional separation: sequences containing adjectives that were the furthest apart in the underlying sequence (i.e., quality – nationality) were often easier than sequences of adjacent adjectives (e.g., colour – nationality). Possible contrastive effects of the L1 Arabic adjective order were also investigated with respect to both MSA and Najdi (the local spoken variety of most participants). Little definite effect was found. These findings supplement and, to some extent, challenge those in other studies that claim greater L1 effects.